Physiological Responses of Switchgrass (Panicum virgatum L.) to Organic and Inorganic Amended Heavy-Metal Contaminated Chat Tailings - A. L. Youngman (Journal of Hazardous Substance Research, 1998)
Study plots established at the Galena subsite of the Cherokee County Superfund Site in southeastern Kansas by the U.S. Bureau of Mines in 1990 were examined during the summer of 1996 to determine whether physiological criteria could be used to determine suitability of switchgrass for remediation of heavy-metal contaminated substrates. Switchgrass was chosen because it was the most frequently encountered species on these plots. Treatment plots included a treatment control, an organic residue treatment of 89.6 Mg ha-1 composted cattle manure, and two inorganic fertilizer treatments recommended for either native grass or grass/legume mixtures. Plant response variables were photosynthetic rate, leaf conductance to water vapor, internal concentration of carbon dioxide in leaves, foliar transpiration rate, leaf water-use efficiency, predawn leaf xylem water potential, and midday leaf xylem water potential. Predawn and midday xylem water potentials were higher for grass/legume inorganic treatment than for the other inorganic treatments. Leaf conductances were lower for organically treated plots than those plots not organically amended and both photosynthesis and transpiration were lower for organically treated plots. Leaf conductances and transpiration were higher for grass/legume treated plots than for plots lacking inorganic treatment. Water-use-efficiency was higher for native grass-treated plots than for other inorganic treatments. Grass/legume inorganic treatment in absence of organic treatment increased predawn and midday xylem water potential, leaf conductance, photosynthesis, and transpiration. Organic amendment in absence of inorganic amendment increased predawn and midday xylem water potential.
Keywords: heavy-metal contamination; switchgrass; remediation